Dinamika Pergolakan Politik di Mesir Abad 20-21 (Sejak Raja Faruq Hingga Muhammad Mursi) - Johan Septian Putra (Tsaqofah dan Tarikh: Jurnal Kebudayaan dan Sejarah Islam, 2022)
Abstract- Egypt since the classical era of Islam to the contemporary era, there have been upheavals that seem endless, especially in the modern era. The political upheaval seems to have become a "culture" that cannot be separated from the Egyptian political community. The purpose of this study is to describe the political dynamics in Egypt in the classical to medieval era and to explain the development of Egyptian politics in the Modern era since the arrival of Europeans to President Morsi in the 21st century. The results of this study are the upheaval of Egypt's political dynamics can not be separated from the role of the military in the flow of democracy and structural government which always experiences gaps and tends not to get finalized, then the transition to changes in Egypt's political form drastically occurred with the revolution of the 20th century by overthrowing the monarchy system. republican system although the democratic side could not be implemented properly since the Nasser era until the Morsi government and ended in 2013.Key Word: Political Dynamics, Political Upheaval, Egyptian Revolution and Military Coup.  Abstrak- Mesir semenjak era klasik Islam hingga era kontemporer telah terjadi pergolakan yang seolah-olah tidak ada habisnya, terutama di era modern. Pergolakan politik tersebut seperti sudah menjadi “budaya” yang tidak terlepas dari masyarakat perpolitikan Mesir. Adapun Tujuan mengkajian materi ini adalah untuk mendeksripsikan dinamika politik di Mesir di era klasik hingga pertengahan dan menjelaskan perkembangan politik Mesir di era Modern sejak kedatangan bangsa Eropa hingga Presiden Mursi di abad ke-21. Hasil penelitian kajian ini adalah pergolakan dinamika politik Mesir tidak terlepas dari peran militer dalam arus demokrasi dan struktural pemerintahan yang selalu mengalami kesenjangan dan cendrung tidak mendapatkan finalisasi kemudian transisi perubahan bentuk politk Mesir secara hebat terjadi dengan adanya revolusi abad ke-20 dengan meruntuhkan sistem monarki kepada sistem republik walaupun sisi demokrasi tidak dapat terlaksanan dengan baik sejak era Nasser hingga pemerintahan Mursi dan berakhir tahun 2013.Kata Kunci: Dinamika Politik, Pergolakan Politik, Revolusi Mesir dan Kudeta Militer.